Transformative Potential: Chatbot GPT-3 and Its Influence Across Industries - Panjavani, Jatin Kumar (International Journal of Computer Sciences and Engineering, 2024)
In recent years, advances in ML (Machine Learning) and AI (Artificial Intelligence) have changed the face of scientific study. Out of all of these, chatbot technology has come a long way in the last few years, especially since ChatGPT became a well-known AI language model. This in-depth study determines ChatGPT`s history, uses, main obstacles, and potential future developments. We start by looking at its history, advancement, and underlying technology before looking at its many uses in a range of industries, such as health care, education, and customer service. The study emphasizes the need to find a balance between human expertise and AI-assisted creativity while also examining potential downsides and ethical quandaries associated with employing ChatGPT in research. The essay addresses several moral issues with the state of computers today and how ChatGPT can cause people to oppose this notion. Furthermore, this work contains several biases and restrictions related to ChatGPT. It is remarkable that despite many difficulties and moral dilemmas, ChatGPT has attracted a lot of attention from researchers, businesses, and academics in a comparatively short amount of time. ChatGPT is a novel technology that can generate natural language answers to input or prompts through the use of state-of-the-art AI algorithms. Applications for it may be found in a range of domains, like content creation, NLP (Natural Language Processing), and customer service. The present analysis and research look into ChatGPT`s functioning, history, and impact on several academic fields. It examines ChatGPT`s advantages and disadvantages as well as its capabilities and limitations. Together with its potential applications for academics and researchers, it also discusses ChatGPT`s implications on information technology, employment, customer service, software development, cyber security, and education.